PTSD among Kidnapped and Raped Women from the Anglophone Regions of Cameroon Related to the Secessionist Armed Conflict - Etarh, Franklin; Österman, Karin (European Journal of Social Science Education and Research, 2024)
The aim of the study was to investigate symptoms of PTSD among women from the Anglophone regions of Cameroon related to the secessionist armed conflict that has been ravaging the regions since 2016.Three hundred and two women from four cities in the restive Anglophone regions of Cameroon and Douala, one of the Francophone regions, completed a questionnaire measuring PTSD. Of the respondents, 55.3 % had been kidnapped, and 36.1 % had been raped during the conflict. A significantly higher percentage of internally displaced women had been victimised compared to others. They also suffered significantly more often from symptoms of PTSD due to the conflict. Both kidnapped and raped women reported significantly higher scores on PTSD than non-victimised women; both groups reported anger and aggression and trouble remembering the conflict. Kidnapped women also reported specifically strong negative feelings like fear, horror, and shame, while raped women reported higher scores on having trouble experiencing positive or loving feelings, and experienced strong physical reactions when reminded of the conflict. The study revealed that PTSD among women from the Anglophone regions of Cameroon was related to victimisation from kidnapping, rape, and internal displacement during the secessionist armed conflict.
Keywords: kidnappings, rape, internal displacement, PTSD, women, Anglophone crisis, Cameroon